2021
DOI: 10.1016/j.celrep.2021.110175
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulator LGP2 targets Ubc13/UBE2N to mediate widespread interference with K63 polyubiquitination and NF-κB activation

Abstract: Highlights d Immune sensor LGP2 is able to inhibit a wide variety of K63 ubiquitin ligases d The target of LGP2 inhibition is the K63 conjugating enzyme, Ubc13/UBE2N d The helicase 2i domain of LGP2 mediates the interaction with Ubc13/UBE2N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…We think that future studies need to further investigate in vitro and in vivo mechanisms underlying function switch of zebrafish LGP2 using knockout technologies. Recent studies have revealed that human LGP2 enhances apoptosis as an antiviral defense mechanism ( Takahashi et al., 2020 ), and LGP2 downregulates innate immune signaling by inhibiting TRAF ubiquitin ligase ( Parisien et al., 2018 ), blocking the interaction between RIG-I and MAVS ( Esser-Nobis et al., 2020 ), and the K63 conjugating enzyme Ubc13 ( Lenoir et al., 2021 ). However, our results showed that zebrafish LGP2 negatively regulates IFN response likely through attenuating tbk1 and ikki mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…We think that future studies need to further investigate in vitro and in vivo mechanisms underlying function switch of zebrafish LGP2 using knockout technologies. Recent studies have revealed that human LGP2 enhances apoptosis as an antiviral defense mechanism ( Takahashi et al., 2020 ), and LGP2 downregulates innate immune signaling by inhibiting TRAF ubiquitin ligase ( Parisien et al., 2018 ), blocking the interaction between RIG-I and MAVS ( Esser-Nobis et al., 2020 ), and the K63 conjugating enzyme Ubc13 ( Lenoir et al., 2021 ). However, our results showed that zebrafish LGP2 negatively regulates IFN response likely through attenuating tbk1 and ikki mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Intrigulingly, it is also important to note that the HEL2i domain is uniquely associated with specialized RNA-activated ATPases (DRAs) that include RNA sensors, RIG-I-like receptors, the ribonuclease Dicer, and DRH-1 and DRH-3 involved in the siRNA pathway of Caenorhabditis elegans ( 9 , 10 , 52 ). Besides its role involved in RNA backbone scanning and binding, the HEL2i domain of Dicer and LGP2 plays a regulatory role in interacting with other cytosolic proteins and their signaling pathways ( 10 , 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, LGP2 disrupts K63-linked ubiquitin chains from transforming into TRIM25 by interacting with Ubc13/UBE2N, which is a K63-Ub-conjugating enzyme from the E2 family. This interaction is also present in two other K63-linked E3s (TRAF6 and RNF125) to negatively regulate innate immune signaling [ 24 , 25 ]. However, accumulating evidence has shown that LGP2 can positively regulate MDA5-mediated antiviral signaling by synergistically sensing viral dsRNA [ 26 , 27 ].…”
Section: Manipulation Of Ring-type E3s In the Rlr And Cgas-sting Path...mentioning
confidence: 99%